Development of an X-Band Reflectarray Antenna for Satellite Communications - Bing Ma (Nature Portfolio, 2021)
Abstract An X-band reflectarray antenna using 16 × 12 double square ring elements for satellite communications is proposed in this paper. The feed is a 4 × 3 elements microstrip patch array designed to create edge taper of approximately − 10 dB. A prototype with right-hand circular polarization (RHCP) is manufactured and tested, and the good agreements between simulations and measurements are demonstrated. The good performance is obtained with the aperture efficiency of 40.7% and the 3-dB gain bandwidth of about 10% which is beneficial to nanosatellites.